ABSTRACT LOCAL CULTURAL ARTS IN THE GLOBAL ERA - Sumantra, I Wayan Deddy; Suastika, I Made; Ardika, I Wayan; Suardiana, I Wayan (E-Journal of Cultural Studies; Vol 14 No 2 (2021): Volume 14, Number 2, May 2021, 2021)
The art of Local culture will be more meaningful because of being able to push the spirit of love with the pluralism toward human's life and universe. Meanwhile, media technology as the physical result of culture that lacks spiritual values ??if compared to custom, religion and art will lose its function to increase human's life quality. Values, norms and ethics contained in customary rules that are reflected in art of culture are indeed useful references in the globalization era. This research used qualitative data that were then analyzed descriptively. According to Alvin Boskoff's thought, it shows that factors becoming challenges for local culture are the change of cultural value systems in society and the death of traditional art forms in several areas in Nusantara caused by technology in the global era. The art of Local culture is one of components that gives Indonesian identity as a special community that exists among nations in this world. Therefore it is necessary to grow awareness particularly in young generations in order to comprehend more about their culture by empowering local wisdom growing in the cultural areas of whole Nusantara. Keywords: Art of Culture, local, the change of value, global